Interview with Dr. Nicté Fabiola Escárzaga: “Bicentennial of Peru and reflections on the peasant movement and its relationship in the armed struggle” - Escudero Camarena, Claudia Isabel (2021)
Nicté Fabiola Escárzaga has a degree in Sociology, a Master’s in Latin American Studies and a PhD in Latin American Studies, also from the National Autonomous University of Mexico. She is a current professor - researcher at the Universidad Autónoma Metropolitana Unidad Xochimilco, and is also a professor of the Postgraduate Course in Latin American Studies at UNAM. His academic interest focuses on the study of indigenous-based armed insurgencies in Mexico, Peru, and Bolivia; Indigenous movement in Latin America; Progressive governments and social movements in Latin America; Indianisms in Latin America; Indigenous education in Mexico and Latin America; and Comparative educational systems in Latin America. She is the author of 12 books published in Mexico and Bolivia, as well as the author of chapters of more than 30 books published in different countries, she also has several scientific articles. In this interview, he shares his reflections on Peru in the context of the Bicentennial against the social and political situation of the country in relation to the peasant movement and the armed struggle. In the same way, he exposes his thinking about the peasant movement in Latin America and how it has evolved in its forms of organization in the face of Peruvian politics, emphasizes Bolivia, Mexico and especially in Peru.